Aprendizagem de uma aluna com TDAH: reflexões sobre inclusão a partir de uma experiência de Estágio Supervisionado - ROSÁRIO, Gabriele Bastos do (2024)
This study results from an experience lived throughout the Supervised Teaching Practice in a public school in Bragança (Brazil, Pará state). That experience occurred in the third year of High School when we observed and analyzed the learner's profile, identifying their difficulties, especially from a student carrying Attention-Deficit/Hyperactivity Disorder (ADHD). This work aims to reflect on the main challenges of learning and teaching the subject of Portuguese to students with ADHD. The methodological process involves a field search based on participant observation, and the data collection with a field diary, using the qualitative perspective. The basis of this work includes some theoretical contributions: Lopes (2018) who talks about the inclusion of historical context; Antunes (2003) who discusses the subject of Portuguese teaching; Mollica et al. (2012) who argue about the literacy of people classified as typical and atypical; Pereira (2016), who talks about the progress of reading practice in children and teenagers with ADHD. We also support this work with the Brazilian inclusion law 13.146/2015, which compiles the rights concerning people with disabilities, and the law 14.254/2021, which guarantees the accompaniment of students with ADHD. The results show the educational activity with the student in school succeeded, although we understand inclusion does not refer only to pedagogical approaches like that; besides, this approach showed itself as convenient for the moment and circumstances. We conclude that this experience supports the professional self-development of the teacher's trainees, and creates the possibility of being close to the challenges and unforeseen situations of the educational environment.